ANALISIS KINERJA PSSI TERHADAP KEPUASAN SUPORTER TIM NASIONAL INDONESIA PERIODE 2024 - Lutfi Nugroho, Vemas; Alyanabilla, Deana; Nur Fauzan, Farhan; Nikita Putri, Larasati; Aditya, Toddy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
In the world of football, supporters play a crucial role and are often referred to as the "12th player." In Indonesia, supporter satisfaction with the national team is a critical factor in building loyalty and engagement. This study aims to investigate the performance of the All Indonesia Football Association (PSSI) and its impact on supporter satisfaction by examining the fundamental question of how PSSI’s performance influences the experience and loyalty of fans. The main objective of this research is to analyze the relationship between PSSI's performance and the level of satisfaction among supporters of the Indonesian national team. A descriptive quantitative approach was used, with primary data collected through questionnaires distributed to 400 respondents who are supporters of the national team. After carrying out the validity test and reliability test, all the results were declared valid and reliable. These findings indicate that PSSI's performance has a positive impact on supporter satisfaction, emphasizing the importance of effective management strategies and engagement to enhance the supporter experience.